A plant-like battery: a biodegradable power source ecodesigned for precision agriculture. Issue 7 (15th June 2022) - Navarro-Segarra, Marina; Tortosa, Carles; Ruiz-Díez, Carlos; Desmaële, Denis; Gea, Teresa; Barrena, Raquel; Sabaté, Neus; Esquivel, Juan Pablo
Abstract : A biodegradable battery inspired by the transpiration pull of liquids in plants has been ecodesigned to power wireless sensors and then be safely biodegraded or composted, resembling the way a plant comes back to nature at the end of its lifecycle. Abstract : The natural environment has always been a source of inspiration for the research community. Nature has evolved over thousands of years to create the most complex living systems, with the ability to leverage inner and outside energetic interactions in the most efficient way. This work presents a flow battery profoundly inspired by nature, which mimics the fluid transport in plants to generate electric power. The battery was ecodesigned to meet a life cycle for precision agriculture (PA) applications; from raw material selection to disposability considerations, the battery is conceived to minimize its environmental impact while meeting PA power requirements. The paper-based fluidic system relies on evaporation as the main pumping force to pull the reactants through a pair of porous carbon electrodes where the electrochemical reaction takes place. This naturally occurring transpiration effect enables to significantly expand the operational lifespan of the battery, overcoming the time-limitation of current capillary-based power sources. Most relevant parameters affecting the battery performance, such as evaporation flow and redox species degradation, are thoroughly studied to carry out device optimization. Flow rates and power outputs comparable to those of capillary-based power sources are achieved. The prototype practicality has been demonstrated by powering a wireless plant-caring device. Standardized biodegradability and phytotoxicity assessments show that the battery is harmless to the environment at the end of its operational lifetime. Placing sustainability as the main driver leads to the generation of a disruptive battery concept that aims to address societal needs within the planetary environmental boundaries.